Hubungan Manajemen Kesehatan Tidak Efektif terhadap Gangguan Pertumbuhan Balita - Didima Ndandirwalu; Muflih Muflih (Journal of Health, 2025)
Parents' negligence in carrying out their responsibilities can cause various problems such as lack of nutritional intake, recurrent infections such as diarrhea and worms, and other health problems that interfere with the growth of toddlers, so health management is needed so that the growth of toddlers remains optimal. To analyze whether there is a relationship between health management and toddler growth. This study used quantitative research with a correlation analytic design and cross sectional method, the population in this study were toddlers aged 7 to 59 months in the working area of Kalasan Health Center with a total of 97 respondents selected using purposive sampling technique consisting of parents of toddlers and cadres who are considered to have important information related to toddler growth and can communicate well. Respondents who were not willing and cadres who were not active in posyandu activities were not involved in the study. Univariate analysis was performed descriptively using frequency distribution, while bivariate analysis used the Chi-Square test. The results showed that 44 respondents (45.4%) were male and 53 respondents (54.6%) were female. A total of 49 toddlers (50.5%) had normal weight and 52 respondents (52.5%) showed effective health management. Chi-Square test results showed that 25 respondents (55.6%) with ineffective health management had impaired growth, with a p value = 0.266 (>0.005), meaning there was no statistically significant association. However, factors such as family income, mother's education, and mother's occupation are known to influence the effectiveness of health management.